Prediabetes conversion to normoglycemia is superior adding a low‐carbohydrate and energy deficit formula diet to lifestyle intervention— a 12‐month subanalysis of the acoorh trial - Roehling, Martin; Kempf, Kerstin; Banzer, Winfried; Berg, Aloys; Braumann, Klaus-Michael; Tan, Susanne; Halle, Martin; Mccarthy, David; Pinget, Michel; Predel, Hans-Georg; Scholze, Juergen; Toplak, Hermann; et al. (Nutrients, 2020)
Lifestyle interventions have been shown to reverse hyperglycemia to normoglycemia. However, these effects are not long‐lasting and are accompanied with high dropout rates. As formula diets have been shown to be simple in usage and effective in improving glycemic control, we hypothesised that adding a low‐carbohydrate and energy deficit formula diet to a low-intensity lifestyle intervention is superior in reversing prediabetes compared with lifestyle intervention alone. In this predefined subanalysis of an international, multicenter randomised controlled trial (Almased Concept against Overweight and Obesity and Related Health Risk (ACOORH) study (ID DRKS00006811)), 141 persons with prediabetes were randomised (1:2) into either a control group with lifestyle intervention only (CON, n = 45) or a lifestyle intervention group accompanied with a formula diet (INT, n = 96). Both groups were equipped with telemonitoring devices. INT received a low‐carbohydrate formula diet substituting three meals/day ( 1200 kcal/day) within the first week, two meals/day during week 2–4, and one meal/day during week 5–26 (1300–1500 kcal/day). Follow‐up was performed after 52 weeks and 105 participants (75%, INT: n = 74; CON: n = 31) finished the 26‐week intervention phase. Follow‐up data after 52 weeks were available from 93 participants (66%, INT: n = 65; CON: n = 28). Compared with CON, significantly more INT participants converted to normoglycemia after 52 weeks (50% vs. 31%; p < 0.05). The risk reduction led to a number‐needed‐to‐treat of 5.3 for INT. Lifestyle intervention with a low‐carbohydrate formula diet reduces prediabetes prevalence stronger than lifestyle intervention alone and is effective for type 2 diabetes prevention.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Formula diet; Lifestyle intervention; Low‐carbohydrate; Multicenter study; Prediabetes; RCT